Long‐term mucocutaneous adverse effects of imatinib in Indian chronic myeloid leukemia patients. (20th December 2017) - Vinay, Keshavamurthy; Yanamandra, Uday; Dogra, Sunil; Handa, Sanjeev; Suri, Vikas; Kumari, Savita; Khadwal, Alka; Prakash, Gaurav; Lad, Deepesh; Varma, Subhash; Malhotra, Pankaj
Abstract: Background: Short‐term mucocutaneous adverse effects are well documented with imatinib. However, studies on long‐term adverse effects and in the ethnic population are lacking. Objective: To study the long‐term mucocutaneous adverse effects of imatinib and factors predicting these adverse effects. Methods: In this cross‐sectional study, consenting adult chronic myeloid leukemia patients on imatinib for more than 250 days were recruited. The details of imatinib treatment were retrieved from hematology clinic records. Results: Four hundred and thirty‐eight patients who were on imatinib for a mean duration of 1820 days were recruited. A mean number of 1.42 ± 0.98 cutaneous adverse effects were seen per patient. Melasma‐like pigmentation, periorbital edema, oral lichenoid reaction, cutaneous hypopigmentation, and vesicobullous eruptions were seen in 236 (53.9%), 81 (18.5%), 70 (16%), 42 (9.6%), and 12 (2.7%) patients, respectively. Drug‐induced cutaneous eruptions (9.1%) and cutaneous hypopigmentation (9.6%) were seen less frequently. Cutaneous hyperpigmentation was more likely seen in younger patients ( P = 0.001) and females ( P < 0.001). On multivariate analysis, female gender was a significant risk factor for developing cutaneous hyperpigmentation and periorbital edema. Conclusion: Cutaneous hyperpigmentation and periorbital edema are common long‐term adverse effects of imatinib in Indian patients. Female gender is a significant risk factor for the development of both these adverse effects.